Anthropogenic Pollution of Aquatic Ecosystems - Häder, Donat-Peter; Helbling, E. Walter; Villafañe, Virginia E. (Springer International Publishing, 2021)
This book provides examples of pollutants, such as accidental oil spills and non-degradable plastic debris, which affect marine organisms of all taxa. Terrestrial runoff washes large amounts of dissolved organic materials from agriculture and industry, toxic heavy metals, pharmaceuticals, and persistent organic pollutants which end up into rivers, coastal habitats, and open waters. While this book is not intended to encyclopaedically list all kinds of pollution, it rather exemplifies the problems by concentrating on a number of serious and prominent recent developments. The chapters in this book also discuss measures to decrease and remove aquatic pollution to mitigate the stress on aquatic organisms. Aquatic ecosystems provide a wide range of ecological and economical services. In addition to providing a large share of the staple diet for a fast growing human population, oceans absorb most of the anthropogenically emitted carbon dioxide and mitigate climate change. As well as rising temperatures and ocean acidification, pollution poses increasing problems for aquatic ecosystems and organisms reducing its functioning and services which are exposed to a plethora of stress factors.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Anthropogenic Pollution; Aquatic Ecosystems; Crude Oil and Plastics; Heavy Metals; Persistent Organic Pollutants; Terrestrial Run-off